Hearing Loss in Israeli Air Force Aviators: Natural History and Risk Factors. Issue 7 (1st July 2016) - Gordon, Barak; Joachims, Zohar; Cohen, Hila Bar; Grossman, Alon; Derazne, Estela; Carmon, Erez; Zilberberg, Michal; Levy, Yuval
ABSTRACT: Objective: To investigate the natural history of hearing loss (HL) in Israeli military aviators and its risk factors. Methods: Audiometric results of aviators with available audiometry at ages 30 and 40 years, and up to their last available audiometry were retrieved. HL definition: pure-tone threshold (PTT) of 30 dB or higher in at least one frequency in at least one ear, moderate-to-severe (M-S) HL as PTT of 45 dB or higher, and suspected noise-induced HL (NIHL) as HL at 3 to 6 kHz. Potential risk factors for HL were assessed by the χ 2 test and logistic regression models. Results: 298 aviators were included. Rates of HL increased with age, up to 57.5% at age 50. All M-S HL at age 50 years had clues on previous examinations, but new HL was observed in all ages. Age was found as a statistically significant risk factor, but aircraft type was not. Total flying hours were found to be an independent risk factor for suspected NIHL only. Self-reported earplug use was not found to protect from HL, with methodological limitations. Conclusions: HL is prevalent in aviators. Age and total flying hours are risk factors, the latter probably only for NIHL, whereas aircraft type is not.